Proposed Exercises As A Precaution Against Osteoporoses and Some Functional, Physical Indicators And Estrogen Hormone In Women aged 45 – 55 - Baqer, Najat (Journal of Physical Education, 2017)
The problem of the research lies in maintaining physical fitness and functional ability in women after menopause (45 – 55) a matter that make them prone to osteoporoses. The researcher designed exercises to develop physical fitness as well as estrogen hormone increase. The researcher used the experimental method. The results were treated using proper statistical operations. The researcher concluded that the proposed exercises have a positive effect on mechanical, functional and physical variables understudy. In addition to that she concluded that these exercises enhance heart muscle efficiency as well as respiratory system improvement. The researcher recommended using the exercises proposed by the researcher to enhance physical and functional traits as well as Making similar researches in mechanical variables and clinical tests as a precaution from osteoporosis.